Privatization in East Germany : A Survey of Current Issues - Bos, Dieter (IMF Working Papers; Working Paper, 1992)
This paper deals with the privatization, restructuring, and liquidation of East German industrial firms. A partnership model is suggested for privatization where the Government's property trust (Treuhandanstait (THA)) is made a silent partner of the private investors. The application of a general scheme of wage subsidies is rejected in the paper. Furthermore, the paper argues against restructuring policies of the Government's property trust and proposes to set decreasing limits on the trust's finances for the years following 1993. The decreasing financial inflow will force the Government's trust to close firms, and will also signal the commitment of the Government to liquidate the trust itself by, say, the year 2000.